Implementation of Montessori Concept in Educating Early Childhood (Case Study of the Role of Early Childhood Education Teachers) (Indonesian Journal of Early Childhood Education Studies, 2022)
As one of the leading figures of early childhood education, Montessori has provided a variety of concepts and thoughts in the development of early childhood education. The purpose of this study is to find out how to implement the concept of the role of teachers in montessori early childhood education in PAUD institutions. This research is qualitative descriptive research with this type of field research. In data collection researchers use interview, observation and documentation techniques. As for analyzing the data, researchers use three steps, namely ranging from data verification, presentation of data to drawing conclusions. The results of this study are the concept of the role of teachers respecting children, teachers respecting child development, teachers as observers, teachers preparing and maintaining the learning environment, teachers as interventions and teachers as catalysts applied by teachers through their role as educators, mentors, facilitators, organizers, evaluators and motivators for children. Keywords: role of teacher, education, early childhood, Montessori